2016
DOI: 10.1161/circimaging.116.005196
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Left Atrial Analysis

Abstract: L eft atrial (LA) size is an important marker for the chronicity of elevated left ventricular (LV) filling pressures and a powerful predictor of adverse cardiovascular outcomes, including stroke, development of atrial fibrillation, congestive heart failure, and death.1 Among the different parameters available for assessing LA size, including diameter, area, and volumes, the latter has been shown to be the most accurate and robust predictor of cardiovascular outcomes.2 Accordingly, a significant amount of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
5
0
2
Order By: Relevance
“…As this method does not implement a specific tool for LA volume analysis, the agreement between 3D and HM results was not assessed . Nevertheless, taking into account the good results obtained for LV end‐diastolic, LV end‐systolic, and LVEF, it is not difficult to assume that the accuracy for LA volume would be similar . Similar results were found by Luo et al in a study with 53 Chinese patients older (mean age 17 years) than the subjects enrolled in the present study but with similar body mass index (21 kg/m 2 ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As this method does not implement a specific tool for LA volume analysis, the agreement between 3D and HM results was not assessed . Nevertheless, taking into account the good results obtained for LV end‐diastolic, LV end‐systolic, and LVEF, it is not difficult to assume that the accuracy for LA volume would be similar . Similar results were found by Luo et al in a study with 53 Chinese patients older (mean age 17 years) than the subjects enrolled in the present study but with similar body mass index (21 kg/m 2 ).…”
Section: Discussionsupporting
confidence: 57%
“…12 Nevertheless, taking into account the good results obtained for LV enddiastolic, LV end-systolic, and LVEF, it is not difficult to assume that the accuracy for LA volume would be similar. 13 Although time has been not analyzed in this study, previous experienced confirmed that HM saves time. 7,14…”
Section: Discussionmentioning
confidence: 86%
“…que o operador selecione manualmente planos ortogonais não encurtados e corrija pequenos erros no traçado das bordas endocárdicas do AE feito pelo software. 5,14 A acurácia da análise dos dados em 3D é altamente dependente da qualidade da imagem, mais do que o 2D. Consequentemente, durante a aquisição de dados, o operador deve reduzir a profundidade da imagem e o ângulo setorial de modo que o AE esteja em foco.…”
Section: Figura 2 -O áTrio Esquerdo Deve Ser Adquirido Usando As Janeunclassified
“…4 Devido a facilidade e alta reprodutibilidade, os laboratórios de ecocardiografia continuam a reportá-la, apesar de serem fortemente desencorajadas nas últimas diretrizes de quantificação das câmaras cardíacas. 4,5 O principal motivo dessa recomendação é que o AE é uma cavidade assimétrica que não se dilata proporcionalmente em todas as direções. Na verdade, o AE tende a se alargar mais na direção craniocaudal do que ântero-posterior devido à presença da coluna e do esterno.…”
Section: Introductionunclassified
“…A recent interest in the malalignment of the left atrial (LA) long axis relative to that of the left ventricle (LV) has surfaced, particularly in relation to its potential implications on LA volume (LAVol) determination by two dimensionaltransthoracic echocardiography (2D-TTE) [1][2][3] which has been used to obtain most normative and predictive LAVol data [1,4,5]. In the clinical practice, the 4-chamber and 2-chamber 2D-TTE views are routinely optimized along the LV long axis such that an unrecognized angulation during scanning may lead to LA foreshortening and underestimation of LAVol by 2D-TTE [1,3,5,6].…”
Section: Introductionmentioning
confidence: 99%